Analysis Of Occupant Satisfaction Level With Performance Of Infrastructure, Facilities, And Utilities In Jongke Apartment Occupancy, Sleman Regency - Harids Irawan (Jurnal Indonesia Sosial Teknologi, 2023)
Rusunawa buildings are vertical residential buildings aimed at low-income people. Although this runaway is specifically for low-income communities, runaway buildings must also meet the requirements for the availability of infrastructure, facilities, and utilities as stipulated in Law Number 20 of 2011 concerning Flats, SNI 03-7013-2004 concerning Procedures for Planning Simple Flats Environmental Facilities. One of the Rusunawa for low-income people is Rusunawa Jongke, Sleman Regency, Yogyakarta Province, which was built in 2012 into a project of the Yogyakarta Public Works, Housing and Settlement Office. Through observations and data collection conducted by researchers in Rusunawa Jongke, Sleman Regency, several requirements regarding infrastructure, facilities, and utilities such as the maximum radius of facilities that are not by the Indonesian National Standard 03-7013-2004 Regarding procedures for planning simple apartment environmental facilities, it is necessary to research to determine the level of occupant satisfaction with the performance of infrastructure, facilities, and utilities of Rusunawa Jongke, Sleman Regency as one of the One evaluation in improving service quality. The Importance Performance Analysis method is used to assess the performance of managers on the performance of infrastructure, facilities, and utilities in Jongke Flats, through the perception of Rusunawa residents. This method compares the level of performance of managers for the performance of Infrastructure, Facilities, and Utilities with the level of expectations or interests of residents of Jongke Rental Simple Flats, Sleman Regency. Overall, the value of occupant satisfaction with the performance of infrastructure, facilities, and utilities in the Jongke Rental Simple Flats, Sleman Regency resulted in an average value of 86%, meaning that the quality of services provided was good but not 100% satisfactory. The level of satisfaction obtained results were Quite Satisfied 16.67%, Satisfied 80%, and Very Satisfied by 3.33%. Drainage facilities and worship facilities are aspects that need to be improved.